The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/joa3.12777
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic therapy after angioplasty of pulmonary vein stenosis due to atrial fibrillation ablation: A two‐center experience and review of the literature

Abstract: Background Pulmonary vein stenosis (PVS) is a severe complication of atrial fibrillation (AF) ablation resulting in narrowing of affected pulmonary veins (PVs). Interventional treatment consists of angioplasty with or without PV stenting. The optimal postprocedural antithrombotic therapy is not known. Study aims To investigate the impact of antithrombotic medical therapy on recurrence of PVS after PV angioplasty. Methods A retrospective study of patients undergoing PV angioplasty with or without stent implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…However, it has been reported that the rate of restenosis in the chronic phase was lower in patients treated with triple therapy. 33 In the present cohort, only 1 patient received triple therapy. It is unclear whether these data are applicable to the Japanese population, which has a high incidence of bleeding events.…”
Section: Postoperative Managementmentioning
confidence: 76%
“…However, it has been reported that the rate of restenosis in the chronic phase was lower in patients treated with triple therapy. 33 In the present cohort, only 1 patient received triple therapy. It is unclear whether these data are applicable to the Japanese population, which has a high incidence of bleeding events.…”
Section: Postoperative Managementmentioning
confidence: 76%
“…We did not use the balloon devices for patients with a common PV trunk or right A lthough pulmonary vein isolation (PVI) has been established as a cornerstone treatment for atrial fibrillation (AF), 1 PV stenosis (PVS) after PVI remains a major complication requiring intervention and is associated with significant morbidity. [2][3][4][5] As the performance of wide encircling PVI using radiofrequency (RF) catheters spread around the world, the incidence of PVS has decreased. However, with the recent development of various balloon devices (e.g., cryoballoon [CB], hot balloon [HB], and laser balloon [LB]), PVS has increased again, because segmental PVI is required.…”
Section: Study Populationmentioning
confidence: 99%